Risk Factors and Prognosis of Cardiorenal Syndrome Type 1 in Elderly Chinese Patients: A Retrospective Observational Cohort Study - Wenxue Hu; Wenna He; Wei Liu; Xiaowu Fang; Yanhua Wu; Feng Yu; Wenke Hao (Karger Publishers, 2016)
Background/Aims: Cardiorenal syndrome type 1 (CRS1) is a syndrome characterized by a rapid worsening of cardiac function leading to acute kidney injury (AKI). The aims of this study were to investigate the risk factors and the prognosis of CRS1 in elderly patients. Methods: A total of 312 elderly patients (≥60 years old) with acute heart failure (AHF) were studied. They were assigned as CRS1 (suffered from in-hospital AKI) or NCRS1 (without AKI) group. Clinical and laboratory data were recorded. Univariate and multivariate analysis were performed to clarify the risk factors for occurrence and mortality of CRS1 in this cohort. Results: Incidence of CRS1 was 52.56%. Basic estimated glomerular filtration (eGFR 2) and use of diuretics were associated with the higher risk of CRS1 in elderly patients (OR=2.239, P=0.025; OR=2.555, P=0.001; respectively). Whereas higher concentration of serum albumin was protective factor for them (OR=0.907, P=0.007). The in-hospital mortality of CRS1 was 23.2%. Dialysis, use of beta blockers or diuretics were associated with all-cause death of CRS1 patients (OR=10.407, PP=0.011; OR=0.345, P=0.040; respectively). The in-hospital mortality of AHF patients was 13.1%. Higher Charlson comorbidity index, occurrence of CRS1 and dialysis were risk factors for in-hospital mortality of AHF patients (OR=4.723, P=0.041; OR=6.096, P=0.008; OR=18.743, PConclusions: Incidence of CRS1 in elderly patients is relatively high and associated with poor outcome. Reduced basic eGFR, lower serum albumin and use of diuretics are risk factors for the occurrence of CRS1 in elderly patients, while use of diuretics, beta blockers and dialysis during hospitalization are predictors of in-hospital mortality in patients with CRS1. These results above suggest that more suitable treatments for the elderly with CRS1 might be needed.